Improved Thermal Resistance and Electrical Conductivity of a Boron-Doped DLC Film Using RF-PECVD - Li, Wanrong; Tan, Xing Yan; Park, Yeong Min; Shin, Dong Chul; Kim, Dae Weon; Kim, Tae Gyu (Frontiers in Materials, 2020)
Diamond-like carbon (DLC) film doped with boron has unique properties and displays higher thermal resistance, lower internal stress, and better electrical conductivity than un-doped DLC film; this makes it is suitable for various applications, especially in outer space. Radio-frequency plasma-enhanced chemical vacuum deposition of boron-doped DLC film was performed to determine the optimal percentage of boron for improving thermal resistance. Additional heat treatment and 40% B2H6/CH4 yielded the best electrical conductivity. X-ray photoelectron spectroscopy, thermal gravimetric analysis, Raman spectroscopy, and the four-point probe method were utilized to analyze the properties of boron-doped DLC film. The boron-doped DLC film displayed outstanding performance in terms of thermal resistance and electrical conductivity.